PERIODONTAL CHANGES IN PATIENTS WITH TYPE 1 DIABETES - CLINICAL ASPECTS - Dora Popescu; Ana Maria Rica; Alexandra Ciuca; Ileana Puiu; Maria Mota; Petra Surlin (Romanian Society of Oral Rehabilitation, 2014)
Diabetes, a pathology that is extremly widespread, involves an alteration homeostasis in the glucose metabolism. Periodontitis is a infectious disease resulting in irreversible destruction of the tooth attachment apparatus. At present, periodontitis is one of the major reasons for adult tooth loss. The periodontal clinical examination determined the following diagnosis categories: chronic gingivitis and chronic periodontitis , all of them being modulated by the systemic disease. Aim of the study is to highlight possible correlations between periodontal status and diabetic clinical parameters characterizing patients diagnosed with type 1 diabetes(T1D). Material and methods This study was conducted on 62 patients. We analysed the general information of the patients and an oral examination for establishing the parodontal diagnosis. The probing depth has been established, number of teeth with pockets Larbert than 6mm and the plaque index Silness and Loe. Results Significant differences were found between the IP values on children and adults but there were no significant differences between IP on GTA and GCA or between IP on GTC and GCC. We did not find a statistically significant correlation between HbA1c and severity of periodontal diagnosis GTC. But found a direct correlation between HbA1c and statistically significant in periodontal diagnosis GTA. Conclusions The results obtained in this study show a possible relationship between metabolic changes caused by periodontal T1D and, especially in the group of adult patients.